2018
DOI: 10.1186/s12886-018-0707-4
|View full text |Cite
|
Sign up to set email alerts
|

Scedosporium apiospermum infectious scleritis following posterior subtenon triamcinolone acetonide injection: a case report and literature review

Abstract: BackgroundUbiquitous fungi of the Scedosporium apiospermum species complex (SASC) cause various opportunistic infections. Posterior subtenon triamcinolone acetonide (STTA) injection is a standard therapy for intraocular inflammation and macular edema. We report a case of Scedosporium apiospermum infectious scleritis after a posterior STTA injection.Case presentationA 75-year-old man received a posterior STTA injection to treat macular edema in his left eye. After 3 months, he complained of ocular pain and hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 29 publications
1
21
0
3
Order By: Relevance
“…Infectious scleritis is a rare complication of sub‐Tenon TA with a reported incidence of 0.04% . A recent review found nine reported cases in which four were caused by fungal organisms …”
Section: Complications Of Ocular and Periocular Steroid Deliverymentioning
confidence: 99%
“…Infectious scleritis is a rare complication of sub‐Tenon TA with a reported incidence of 0.04% . A recent review found nine reported cases in which four were caused by fungal organisms …”
Section: Complications Of Ocular and Periocular Steroid Deliverymentioning
confidence: 99%
“…[ 74 ] The most common fungi that may cause scleritis are filamentous fungi. Aspergillus flavus is the most frequent fungus isolated, but several other species can cause infection[ 75 76 77 78 ]…”
Section: Types Of Infectious Scleritismentioning
confidence: 99%
“…Subtenon injection of triamcinolone acetonide (STTA) has been widely adopted to treat macular oedema secondary to diabetic retinopathy, branch retinal vein occlusion (BRVO), and uveitis. Although infectious complications following STTA are uncommon, endophthalmitis [21], scleritis [22,23], and orbital abscess [21,[24][25][26][27][28] have been reported. Furthermore, only two cases of fungal orbital abscess following STTA were found to have been reported so far [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%